Evaluasi Usability Website Pelacakan Bus Listrik Medan Menggunakan Metode System Usability Scale (SUS) pada Mahasiswa UINSU - Cindy Anggriani; Muhammad Irwan Padli Nasution (CV. Multi Kreasi Media, 2026)
The Medan electric bus tracking website serves as a real-time information source for bus departure schedules. This study examined how users interact with the platform by involving digitally literate students from the State Islamic University of North Sumatra (UINSU). Thirty-two participants accessed the tracking feature on buslistrikmedan.com and completed the System Usability Scale (SUS) assessment afterward. The results show that although the interface is simple, the navigation flow and response speed still limit user comfort. These findings highlight the need to refine interface structure and improve information clarity to ensure a more efficient and convenient tracking experience.